Analisis Faktor – Faktor Kesulitan Belajar Pada Peserta Didik Kelas 8 Di SMP Muhammadiyah Waipare - Irnawati, Irnawati (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study is to find out the difficulty learning factors. The framework of this research is students should be able to concentrate and maintain their learning well. To get the maximum learning result, students should not get difficulties in learning process. For that reason, this study desire to analyze the students’ difficulty learning factors. After analyzing the factors, the solution can be taken to solve all problems. This research used descriptive qualitative method. Qualitative data analysis is used to analyze these qualitative data. Qualitative data serve some information related to the difficulties faced by students, understanding level of a subject (cognitive aspect), teaching learning process, students’ attitude (affective), students’ enthusiasm, and students’ motivation. This research is focused on the students’ difficulties learning factors. The students of 8 diSMP Muhammadiyah Waipare is chosen as respondent. Techniques of data collection are interview, observation, and documentation. Data analysis is followed the qualitative research principle. The result of this research shows that the students of 8 diSMP Muhammadiyah Waipare get difficulties in learning process which influenced by internal and external factors